A study on Arch Widths of Bangladeshi Adult Subjects with Class II-2 malocclusion compared to those with Class II div1 malocclusion and Normal Occlusion (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Aim : To evaluate the transverse discrepancy in different malocclusion groups. Also to test the hypothesisvthat models with Class II division 2 malocclusion may have mean maxillary arch widths significantly smaller than those with normal occlusions and significantly larger than those with Class II division 1 malocclusion. Thus the proposed study will generate interest among the orthodontists for further study over the transverse discrepancy of our patients and guide them to establish effective treatment strategy and their management.Methods:  This study was a cross  sectional  study conducted among the dental casts of 150 patients and  students of the Department of Orthodontics and Dentofacial Orthopedics, Dhaka Dental College and  Hospital. Both male and female were included.  The first group consists of 50 pair of study models with  permanent dentition and diagnosed as Class I (normal) occlusion. The second group includes another 50 pair of dental casts with permanent dentition and diagnosed as Class II division 1 malocclusion . And third group includes another 50 pair of dental casts with permanent dentition and was diagnosed as Class II division 2 malocclusion. This group of malocclusion was again subdivided into two categories, Class II division 2 malocclusion with crowding and Class II division 2  malocclusion without crowding. The Students t test was used to analyze the data. In this analytical test the level of significance p value